E-036 Utilisation of the Navien Distal Intracranial Catheter During 78 Cases of Anterior Circulation Aneurysm Treatment with the Pipeline Embolisation Device. (14th July 2013) - Colby, G; Lin, L; Huang, J; Tamargo, R; Coon, A
Abstract : Background: Endovascular treatment of intracranial aneurysms relies on coaxial catheter support systems to provide safe and stable access. Large bore distal intracranial catheters have become necessary for aneurysm treatment with flow diverting devices, including the Pipeline embolisation device (PED). These catheters must accommodate 0.027″ microcatheters, be supple enough to track distally, and be able to provide sufficient support for manipulations required for PED deployment. Methods: A single-centre aneurysm database was reviewed to identify patients who underwent anterior circulation aneurysm embolisation with the PED while utilising the Navien distal intracranial catheter. Data were collected regarding the equipment used, cervical internal carotid artery (ICA) tortuosity, intra-procedural Navien positions, and peri-procedural complications. Results: The Navien catheter (5F, 0.070″ OD, 0.058″ID, 115 cm) was used in 78 anterior circulation PED cases. The Navien was tracked into position over a Marksman in 76/78 cases (97%). The final catheter tip position was in the cervical ICA (1/78, 1%), petrous ICA (23/78, 30%), proximal cavernous ICA (48/78, 62%), distal cavernous/clinoidal ICA (3/78, 4%), supraclinoid ICA (2/78, 2%), and the M1 segment (1/78, 2%). In each case, the catheter was tracked to its desired position (100% clinical success) despite significant proximal vessel tortuosity in 34 cases (44%). No clinically significant catheter related complications occurred. Conclusion: The Navien intracranial catheter is an important component of the tri-axial system for embolisation of cerebral aneurysms with the PED. This catheter is highly trackable to distal positions, atraumatic, and provides sufficient support for the microcatheter manipulations used during typical PED deployments. Disclosures: G. Colby: None. L. Lin: None. J. Huang: None. R. Tamargo: None. A. Coon: 2; C; Covidien.